Mucinous Cystadenoma: A Rare Hepatic Tumor in a Child - Ferraguti, Danielle A.; McGetrick, Molly; Zendejas, Ivan; Hernandez-Gonzalo, David; Gonzalez-Peralta, Regino (Frontiers in Pediatrics, 2017)
Mucinous cystadenomas (MCAs) of the liver (also called hepatic biliary cystadenomas) are rare tumors that comprise about 5% of cystic masses of the liver in adults. These slow-growing lesions most commonly occur in middle-aged individuals, with a female sex predominance. Herein, we present a MCA in a six-year-old male, one of only very few such cases described in the pediatric literature to date. Although MCAs are generally considered benign lesions, malignant transformation rarely occurs. The recurrence rate is high when partial cyst excision is performed. Therefore, complete surgical cyst resection with clinical follow-up, including imaging, is warranted.